Pengaruh Latihan Circuit Training Terhadap Ketepatan Bowling Off Spin Atlet Unimed Cricket Club (UCC) - Anggun Amalia Sembiring; Sanusi Hasibuan (Universitas Batanghari Jambi, 2026)
This study aims to determine the effect of circuit training on the accuracy of bowling off spin of unimed cricket club (UCC) athletes. Circuit training is a form of training that has a pattern of combining several types of exercises in one training session. Circuit training is a form of training that is able to increase the accuracy of bowling off spin if it is arranged properly and correctly, so that it is able to achieve training goals well. This study is an experimental research with the pretest - posttest one group approach method. The subjects in this study were 18 athletes from the unimed cricket club (UCC). This research was conducted on jl. William Iskandar Pasar V Medan Estate. The instrument used is the bowling off spin test. Data analysis techniques by testing the normality of data and testing the hypothesis t. Based on the results of the research conducted, it was obtained from the initial average score of 6.00 to 11.28 which if presented with the percentage of pretest was at 33.33% and posttest at 62.67% which when viewed there was an increase of 29.33%. This means that circuit training can increase the accuracy of UCC athletes' bowling off spin by 29.33%. From this data, tcount (10,480) > ttable (2,110), which means that the alternative hypothesis (Ha) which reads